Reproductive seasonality and maturation of the sergestid shrimp, Acetes japonicus (Decapoda: Sergestidae) in coastal waters of Malacca, Peninsular Malaysia - Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Siraj, Siti Shapor; Bujang, Japar Sidik (Academic Journals, 2010)
Sex ratio, length at first maturity and spawning season of the sergestid shrimp (Acetes japonicus) were investigated between April 2006 and March 2007 in coastal waters of Klebang Besar, Malacca, Peninsular Malaysia. Klebang Besar waters are one of the main fishing grounds for A. japonicus in the Peninsular Malaysia. The overall annual sex ratio was found to be 1:1.46 (males: females). The spawning season was March to July with peak in May, however there was also some spawning in October to November. The female attained sexual maturity at a minimum size of 17.5 mm total length. The matured and near to spawn stages (II and III) occurred more than 50% in every month except in August. Therefore, it may be inferred that A. japonicus breeds continuously throughout the year in the coastal waters of Malacca, Peninsular Malaysia.